Analisis Fiqh Muamalah Tentang Sistem Penjaminan Tanggung Renteng Pembiayaan Kelompok - Enceng Iip Syaripudin; Bung Hijbullah Sulthonudin (Jurnal Hukum Ekonomi Syariah, 2026)
This research is motivated by the practice of the joint liability system in group financing, which is commonly used by cooperatives but has raised practical issues in the field. The main problem lies in the implementation mechanism of this system and its relevance to the principles of Islamic commercial jurisprudence (Fiqh Muamalah). The purpose of this study is to examine how the joint liability system operates, provide recommendations to improve its effectiveness, and analyze it from a Fiqh Muamalah perspective. This study employs a qualitative method through a field research approach, using data collection techniques such as observation and interviews. The results show that the implemented joint liability system does not fully align with the principles of mutual assistance (ta’āwun) and mutual consent (antarāḍin) in Fiqh Muamalah. In practice, members who initially agreed to share liability often feel disadvantaged because they must cover the arrears of others, leading to potential conflicts. This system creates a social burden for punctual members and may increase delinquencies due to a lack of individual responsibility. Keywords: Muamalah; Guarantee; Joint Liability; Financing; Group